Polimorfizm genu ACTN3 w sporcie i fizjoterapii = CTN3 gen polymorphism in sport and physiotherapy - Zawadka, Magdalena; Michalik, Joanna (Journal of Education, Health and Sport, 2016)
Zawadka Magdalena, Michalik Joanna. Polimorfizm genu ACTN3 w sporcie i fizjoterapii = CTN3 gen polymorphism in sport and physiotherapy. Journal of Education, Health and Sport. 2016;6(8):219-226. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60224 http://ojs.ukw.edu.pl/index.php/johs/article/view/3750 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016. Polimorfizm genu ACTN3 w sporcie i fizjoterapii ACTN3 gen polymorphism in sport and physiotherapy Magdalena Zawadka1, Joanna Michalik2 1 Ośrodek Rehabilitacji, Instytut Medycyny Wsi im. Witolda Chodźki, Lublin 2 NZOZ Sanus, Lublin Autor do korespondencji: Magdalena Zawadka Instytut Medycyny Wsi, ul. Jaczewskiego 2, 10-090 Lublin magdalenazawadka91@gmail.com Tel. 517967452 Streszczenie Czynniki genetyczne mogą wpływać na wyniki sportowe. Genotyp ACTN3 R577X został powiązany z wynikami sportowymi i fenotypem mięśniowym. Gen ACTN3 kodujący białko α-aktynina-3, który ulega ekspresji w linii Z szybkich, glikolitycznych włókien mięśniowych ma związek z mocą i siłą. Czynniki genetyczne są zaangażowane w etiologię urazów tkanek miękkich i funkcjonowanie układu krążenia. Celem naszej pracy było zaprezentowanie przeglądu literatury. Niniejsze badanie pokazuje jak polimorfizm R577X ACTN3 może wpływać na wyniki sportowe i wystąpienie urazów. Jest wyraźnie ukazane, że czynniki genetyczne mogą mieć wpływu na trening sportowy i fizjoterapię. Słowa kluczowe: genetyka, włókna mięśniowe, urazy tkanek miękkich. Summary Genetic factors can interfere with sporting performance. The ACTN3 R577X genotype has been associated with athletic results and muscle phenotypes. The ACTN3 gene that encodes the α-actinin-3 protein, which is, only expressed in the Z line of fast glycolytic muscle fibres was found to associate with power/strength performance. Genetic factors are implicated in the etiology of soft tissue injuries and function of cardiovascular system. The aim of our study was to present review of literature. It is demonstrated in this study how R577X polymorphism in ACTN3 could influence on sport results and occurrence of injuries. It is clearly shown , that genetic factors may have implication in sport training and physical therapy. Key words: genetics, muscle fibers, soft tissue injuries.